Targeting HIV-1 conserved regions: An immunoinformatic pathway to vaccine innovation for the Asia - Akmal Zubair; Ahmed Al-Emam; Muhammad Ali; Syeda Maryam Hussain; Ranya Mohammed Elmagzoub (PLoS ONE, 2025)
A combination of humoral and cell-mediated immune system stimulation is essential for developing an effective HIV vaccine. Traditional treatment options and the challenges posed by drug resistance necessitate the discovery of a viable vaccine candidate capable of eliciting a robust immunological response. This research aims to develop an HIV vaccine with a multi-epitope component using a unique immunoinformatics approach. A subunit vaccine comprising B-cell, helper T-cell, and cytotoxic T-cell epitopes, along with appropriate adjuvants and linkers, was employed to identify conserved regions in the Pol, Vpr, Gag, Tat, Env, Nef, and Vif proteins. The HIV subunit vaccine demonstrated the potential to activate both cell-mediated and humoral immune responses, indicating its immunogenicity. The application of homology modeling and refinement further enhanced the model’s accuracy. Subsequently, the molecular docking procedure utilized the refined model structure to bind to the immunological receptor TLR-3 in lymphocyte cells. Following this, the potential interactions of the subunit vaccine with TLR-3 were investigated using molecular dynamics modeling. The vaccine’s stability was improved through a meticulous disulfide engineering technique that involved inserting cysteine residues into highly flexible regions. Finally, in silico cloning was employed to validate the efficacy of translating and producing the vaccine in a microbiological setting. The vaccine shows promising results in terms of population coverage, reaching 82% of the global population, with extraordinary efficacy in Asia, covering up to 95% of the population. Our HIV vaccine candidate is highly stable and elicits a robust immune response against HIV-1.